Strategi Optimalisasi Pemanfaatan Lahan Pada Kawasan Terdampak Lumpur Sidoarjo - Muhammad Fakhri Syukri; Dzaki Naufal Hakim; Yahdi Isnu Miftahuddin (COMPACT: Spatial Development Journal, 2023)
The Sidoarjo mudflow that has occurred since 2006 is a natural event that leads to a geothermal phenomenon. The Sidoarjo mudflow raises the potential for deformation in the form of other geological disasters in the surrounding area, including symptoms of land subsidence, land rise and land shift. One of them causes a decrease in the carrying capacity of the environment due to the emergence of deformations that damage the ecosystem structure, especially rice fields around the location of the eruption. This causes a decrease in land values ​​and changes in the livelihoods of the surrounding community. Thus, the government needs to make efforts in handling environmental, socio-cultural, and economic aspects with the aim of changing the existing conditions of a very limited environment towards a new balance. Therefore, this study aims to formulate a strategy for optimizing land use in the radius affected by the Sidoarjo mud which focuses on the area affected by the Sidoarjo mud. The data collection method in this study was conducted primarily through interviews with stakeholders as well as secondary data collection from a number of related agencies and literature studies. The analytical method used consists of spatial analysis in the form of overlapping the physical aspects, legal aspects and financial/economic aspects of the area. Based on the results of the analysis, obtained a typology of land with high, medium and low vulnerability and protected. Planning and utilization directions on land with a high vulnerability typology can be developed into built-up land, land with a moderate typology can be developed into limited built-up land and land with a low-vulnerability typology will be maintained as rice fields, as well as in protected areas not to be converted. The results of this study can be used as input for the government of Sidoarjo Regency when preparing the spatial plan, so that in terms of implementing the plan and utilizing the space, it consider the conditions and maintain the existing ecosystem.